First Report of Dieback Caused by Lasiodiplodia theobromae in Strawberry Plants in Korea - Nam, Myeong Hyeon (Mycobiology, 2016)
Dieback in strawberry (Seolhyang cultivar) was first observed during the nursery season (June to September) in the Nonsan area of Korea in the years 2012 and 2013. Initial disease symptoms included dieback on runners, as well as black rot on roots, followed by wilting and eventually blackened, necrotic discoloration in the crowns of daughter plants. A fungus isolated from the diseased roots, runners, and crowns is close to Lasiodiplodia theobromae based on morphological characteristics. Analysis of a combined dataset assembled from sequences of the internal transcribed spacer and translation elongation factor 1-alpha genes grouped nine fungal isolates with the type strain of L. theobromae. The isolates showed strong pathogenicity on strawberry cultivars Kumhyang, Seolhyang, and Akihimae, fulfilling Koch's postulates. Based on these results, the pathogen responsible for dieback on strawberry plants in Korea was identified as L. theobromae.